An ultrahigh hydrophobicity silica aerogel composite material and a preparation method thereof
Patent Information
- Application Number
- CN202610899260.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-22
- Publication Date
- 2026-10-09
AI Technical Summary
该方法制备的气凝胶疏水性能优于共前驱体法,但由于二氧化硅湿凝胶内部存在大量充满空气和残留有机物的微小孔隙,会产生“气阻”效应,严重阻碍改性剂渗透到材料内部,导致材料出现“表面疏水、内部亲水”的现象,影响其长期使用性能和隔热效果
1、本发明通过在二次后处理改性过程中引入负压环境(≤-0.03MPa),将二氧化硅湿凝胶内部孔隙中的空气和残留有机物完全抽出,消除了“气阻”效应,使疏水改性剂能够在大气压作用下快速、充分地渗透到材料内部的所有孔隙中,与暴露的≡Si-OH发生接枝反应,实现了材料从表面到内部的均一高憎水性,有效解决了常规二次后处理改性法“表面疏水、内部亲水”的问题。
Smart Images

Figure CN122878110A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aerogel material preparation technology, specifically relating to an ultra-high hydrophobic silica aerogel composite material and its preparation method. Background Technology
[0002] Silica aerogel possesses a unique three-dimensional nanoporous structure (pore size 20-50 nm) and is currently the solid material with the lowest known thermal conductivity, making it widely used in building energy conservation, industrial pipeline insulation, aerospace, and other fields. In special applications such as offshore oil refineries, polar research, and special equipment, silica aerogel composites are required to have ultra-high hydrophobicity to prevent moisture absorption and icing in ultra-low temperature environments, thereby maintaining their ultra-low thermal conductivity and lightweight properties.
[0003] In existing technologies, the main methods for imparting hydrophobicity to silica aerogels are the co-precursor method (in-situ polymerization) and the secondary post-treatment modification method. The co-precursor method involves simultaneously hydrolyzing an alkyl-containing organosilicon source (R-Si-(OR)3) and a non-alkyl-containing organosilicon source (Si-(OR)4), allowing the alkyl groups to be grafted in situ onto the silica framework, thus giving the aerogel its inherent hydrophobicity. However, the steric hindrance of the alkyl groups in this method makes the hydrolysis reaction difficult to control, affecting the gelation time and the spatial network structure of the aerogel. Ultimately, the overall performance of the prepared aerogel is far inferior to that obtained through the secondary post-treatment modification method.
[0004] The secondary post-treatment modification method involves immersing a silica wet gel in a hydrophobic modifier solution. The (CH3)3-Si- in the modifier reacts with the HO-Si≡ on the aerogel surface to form R3-Si-O-Si≡, thus imparting hydrophobicity to the material. Aerogels prepared by this method exhibit better hydrophobic properties than those prepared using the co-precursor method. However, due to the presence of numerous tiny pores filled with air and residual organic matter within the silica wet gel, an "air barrier" effect occurs, severely hindering the penetration of the modifier into the material's interior. This results in a "hydrophobic surface, hydrophilic interior" phenomenon, affecting its long-term performance and thermal insulation effect.
[0005] To address these issues, some researchers have attempted to increase the penetration depth of the modifier by extending the impregnation time. However, this increases the production cycle and still fails to achieve uniform hydrophobicity inside and outside the material. Summary of the Invention
[0006] To address the aforementioned problems, the present invention aims to provide an ultra-high hydrophobic silica aerogel composite material and its preparation method, which enables the modifier to quickly and fully penetrate into the interior of the material, achieving uniform ultra-high hydrophobicity both inside and out, while simultaneously reducing the thermal conductivity of the material and improving its thermal insulation performance.
[0007] This invention is achieved through the following technical solution: A method for preparing an ultra-high hydrophobic silica aerogel composite material includes the following steps: S1: Preparation of organosilicon sol: Mix organosilicon source, alcohol reagent and water, add pH acidity adjuster to adjust the pH of the solution to 3, heat and stir at 40℃ for 5 hours to obtain organosilicon sol; S2: Preparation of silica wet gel composite material: The gel catalyst and the organosilicon sol obtained in step S1 are mixed and stirred in a constant temperature container at 40℃ for 1 min at a volume ratio of 1: (8~15). Fiber felt is then placed in the container and completely immersed in the organosilicon sol. The mixture is left to stand for 3-5 min to obtain silica wet gel composite material. S3: Negative pressure secondary post-treatment modification: The silica wet gel composite material obtained in step S2 is placed in a constant temperature sealed device at 40℃, and the device is evacuated until the pressure inside the device is ≤-0.03MPa. A mixture of hydrophobic modifier and alcohol reagent is introduced, and solvent replacement aging is carried out under negative pressure for 12 hours. S4: Supercritical CO2 drying: The wet gel composite material modified in step S3 is placed in a supercritical drying kettle, and solvent replacement is performed using supercritical CO2 fluid drying technology to obtain an ultra-high hydrophobic silica aerogel composite material.
[0008] Further, in step S1, the volume ratio of the organosilicon source to the alcohol reagent is 1:5; the organosilicon source is selected from one of tetraethyl orthosilicate, methyl orthosilicate, and polymethyl silicate; the pH acidity adjuster is selected from one of hydrochloric acid, nitric acid, and acetic acid.
[0009] Furthermore, the volume ratio of the organosilicon source to water in step S1 is 10:3.
[0010] Further, the gel catalyst in step S2 is selected from one or two of sodium bicarbonate, ammonium bicarbonate, ammonia, and ammonium fluoride solution; the fiber mat is selected from one of wet-process ceramic paper, wet-process glass fiber mat, melamine foam, pre-oxidized fiber mat, and glass fiber mat.
[0011] Furthermore, the sealing device in step S3 is a thermostatic stainless steel tank with multiple valves; the alcohol reagent is selected from methanol and ethanol; and the hydrophobic modifier is hexamethyldisilazane.
[0012] Furthermore, the volume ratio of the alcohol reagent to the hydrophobic modifier in step S3 is 500:1.
[0013] Furthermore, the mixture of hydrophobic modifier and alcohol reagent described in step S3 is introduced by self-priming through the pressure difference between atmospheric pressure and the sealing device.
[0014] Furthermore, the process parameters for supercritical CO2 fluid drying in step S4 are: pressure 14 MPa, temperature 50-60℃, CO2 flow rate 2300 kg / h, and drying cycle time 4 hours.
[0015] The beneficial effects of this invention are: 1. This invention introduces a negative pressure environment (≤-0.03MPa) during the secondary post-treatment modification process to completely extract air and residual organic matter from the pores inside the silica wet gel, eliminating the "air resistance" effect. This allows the hydrophobic modifier to quickly and fully penetrate into all the pores inside the material under atmospheric pressure, and undergo a grafting reaction with the exposed ≡Si-OH. This achieves uniform high hydrophobicity of the material from the surface to the interior, effectively solving the problem of "hydrophobic surface and hydrophilic interior" in conventional secondary post-treatment modification methods.
[0016] 2. The silica aerogel composite material prepared by this invention has excellent performance. Its water absorption rate at 30 min is significantly lower than that of materials prepared by existing technologies, and its thermal conductivity is significantly reduced. Under the same hot surface temperature conditions, its cold surface temperature is significantly lower than that of materials prepared by existing technologies, thus improving its thermal insulation performance.
[0017] 3. The preparation process of this invention is simple and controllable, requires no complex equipment, and is easy to mass-produce industrially. The prepared composite material is suitable for fields with strict requirements for high hydrophobicity and excellent thermal insulation performance, such as offshore oil refineries, aerospace, polar scientific research, and special equipment. Attached Figure Description
[0018] The present invention will now be described in further detail with reference to the accompanying drawings.
[0019] Figure 1 This is a schematic diagram of the preparation process of the ultra-high hydrophobic silica aerogel composite material described in this invention.
[0020] Figure 2 The cold surface temperature of silica aerogel composites prepared by different hydrophobic modification methods varies with time. Detailed Implementation
[0021] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification.
[0022] It should be noted that the terms “comprising,” “including,” or any other variations are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus. Example 1
[0023] This embodiment provides a method for preparing an ultra-high hydrophobic silica aerogel composite material. The specific steps are as follows: S1: Preparation of organosilicon sol: 1L of methyl orthosilicate, 5L of methanol, and 300mL of deionized water are added to a reaction vessel and stirred evenly. Hydrochloric acid is added to adjust the pH of the mixed solution to 3. The mixture is heated and stirred at a constant temperature of 40℃ for 5 hours to fully hydrolyze the methyl orthosilicate and obtain a transparent and uniform organosilicon sol. S2: Preparation of silica wet gel composite material: Ammonia water (gel catalyst) and the organosilicon sol obtained in step S1 are added to a gel frame at a volume ratio of 1:(8~15) at 40℃ and stirred for 1 minute to mix evenly. Pre-oxidized fiber felt is quickly placed in the mixture and completely immersed in the organosilicon sol. The temperature is kept constant and the mixture is allowed to stand for 3-5 minutes until the sol is completely gelled to obtain a silica wet gel composite material. S3: Negative pressure secondary post-treatment modification: The silica wet gel composite material obtained in step S2 is transferred to a constant temperature stainless steel sealed container at 40℃. The vacuum pump is turned on to evacuate the sealed container until the pressure inside the container reaches -0.03MPa. Then, a methanol solution of hexamethyldisilazane (methanol to hexamethyldisilazane volume ratio 500:1) is introduced through a valve using the pressure difference. The container is then left to stand under a negative pressure of -0.03MPa for solvent replacement aging for 12 hours. S4: Supercritical CO2 drying: The wet gel composite material modified in step S3 is taken out and placed in a supercritical drying kettle. The drying parameters are set as follows: pressure 14MPa, temperature 55℃, CO2 flow rate 2300kg / h, and drying cycle time 4 hours. After drying, the composite material is taken out to obtain an ultra-high hydrophobic silica aerogel composite material.
[0024] Comparative Example 1 (Common Precursor Method) This comparative example uses a co-precursor in-situ polymerization method to prepare hydrophobic silica aerogel composite material. The specific steps are as follows: 1 L of methyl orthosilicate, 5 L of methanol, 0.2 L of methyltrimethoxysilane (in-situ hydrophobic modifier) and 400 mL of deionized water are added to a reaction vessel and stirred evenly. Then, hydrochloric acid is added to adjust the pH of the mixed solution to 3. The mixture is heated and stirred at a constant temperature of 40°C for 5 hours to obtain an organosilicon sol. The subsequent gelation, aging and drying steps are the same as in Example 1. The aging step involves placing the wet gel in a container filled with methanol at 40°C and allowing it to stand for 24 hours to age. Finally, the hydrophobic silica aerogel composite material is obtained.
[0025] Comparative Example 2 (Atmospheric Pressure Secondary Post-treatment Modification Method) This comparative example uses a conventional atmospheric pressure two-stage post-treatment modification method to prepare hydrophobic silica aerogel composite material. The specific steps are as follows: Steps S1 and S2 are exactly the same as in Example 1, and a silica wet gel composite material is obtained; S3: Atmospheric pressure modification: The wet gel composite material is placed in a container at 40°C, and a hexamethyldisilazane methanol solution of the same concentration as in Example 1 is added. The mixture is allowed to stand under atmospheric pressure for 24 hours for modification; S4: The supercritical CO2 drying step is the same as in Example 1, and finally, a hydrophobic silica aerogel composite material is obtained.
[0026] Performance testing The following performance tests were performed on the silica aerogel composite materials prepared in Example 1, Comparative Example 1, and Comparative Example 2: Thermal conductivity test: The hot wire method was used, and the test was conducted in accordance with the GB / T10294-2008 standard. Water absorption test: Cut the sample into 100mm×100mm×10mm specimens and weigh the initial mass (m). a Then, completely immerse the sample in deionized water at 25℃. After 30 minutes, remove it, gently blot the surface moisture with filter paper, weigh the sample (m1), and calculate the water absorption rate after 30 minutes: Water absorption rate = (m1 - m a ) / m a ×100%; Thermal insulation performance test: The sample was made into a specimen with a thickness of 20 mm. A flame thermal insulation test device was used, the hot surface temperature was set to 675℃, and the pressure was maintained at 0.9 MPa for 5 min. Then the pressure was released to 0.03 MPa and maintained for 25 min. The change of cold surface temperature over time was recorded within 30 min.
[0027] Table 1 shows a performance test comparison between Example 1 and Comparative Examples 1 and 2: Table 1
[0028] As can be seen from Table 1, the thermal conductivity and 30-minute water absorption rate of the composite material prepared in Example 1 of the present invention are significantly lower than those of Comparative Example 1 and Comparative Example 2. Specifically, the 30-minute water absorption rate is only 2.1%, which is 48.8% of that of Comparative Example 2 and 19.3% of that of Comparative Example 1; the thermal conductivity is 14.0% lower than that of Comparative Example 2 and 38.5% lower than that of Comparative Example 1.
[0029] Internal hydrophobicity test: The composite material prepared in Example 1 was layered along the thickness direction, and a sample of the inner layer with a thickness of 0.75 mm was taken. The water absorption rate was tested for 30 minutes according to the water absorption rate test method described above; Table 2 shows the internal hydrophobicity test results of Example 1:
[0030] Table 2 As can be seen from Table 2, the 30-minute mass water absorption rate of the 0.75mm thick inner layer of the composite material in Example 1 is only 1.3%, which is close to the surface water absorption rate. This indicates that the modifier has fully penetrated into the interior of the material, achieving uniform ultra-high hydrophobicity inside and out.
[0031] from Figure 2 The temperature change curve of the cold side shows that, under the same hot side temperature and test conditions, the cold side temperature of Example 1 is always lower than that of Comparative Example 1 and Comparative Example 2. At 30 min, the cold side temperature is about 20°C lower than that of Comparative Example 2 and about 50°C lower than that of Comparative Example 1, indicating that the thermal insulation performance of the composite material prepared by the present invention is significantly better than that of the prior art.
[0032] The scope of protection of this invention is not limited to the technical solutions disclosed in the specific embodiments. Any modifications, equivalent substitutions, improvements, etc., made to the above embodiments based on the technical essence of this invention shall fall within the scope of protection of this invention.
Claims
1. A method for preparing an ultra-high hydrophobic silica aerogel composite material, characterized in that: Includes the following steps: S1: Preparation of organosilicon sol: Mix organosilicon source, alcohol reagent and water, add pH acidity adjuster to adjust the pH of the solution to 3, heat and stir at 40℃ for 5 hours to obtain organosilicon sol; S2: Preparation of silica wet gel composite material: The gel catalyst and the organosilicon sol obtained in step S1 are mixed and stirred in a constant temperature container at 40℃ for 1 min at a volume ratio of 1: (8~15). Fiber felt is then placed in the container and completely immersed in the organosilicon sol. The mixture is left to stand for 3-5 min to obtain silica wet gel composite material. S3: Negative pressure secondary post-treatment modification: The silica wet gel composite material obtained in step S2 is placed in a constant temperature sealed device at 40℃, and the device is evacuated until the pressure inside the device is ≤-0.03MPa. A mixture of hydrophobic modifier and alcohol reagent is introduced, and solvent replacement aging is carried out under negative pressure for 12 hours. S4: Supercritical CO2 drying: The wet gel composite material modified in step S3 is placed in a supercritical drying kettle, and solvent replacement is performed using supercritical CO2 fluid drying technology to obtain an ultra-high hydrophobic silica aerogel composite material.
2. The preparation method according to claim 1, characterized in that: In step S1, the volume ratio of the organosilicon source to the alcohol reagent is 1:5; the organosilicon source is selected from one of tetraethyl orthosilicate, methyl orthosilicate, and polymethyl silicate; the pH acidity adjuster is selected from one of hydrochloric acid, nitric acid, and acetic acid.
3. The preparation method according to claim 1, characterized in that: The volume ratio of the organosilicon source to water in step S1 is 10:
3.
4. The preparation method according to claim 1, characterized in that: The gel catalyst in step S2 is selected from one or two of sodium bicarbonate, ammonium bicarbonate, ammonia, and ammonium fluoride solution; the fiber mat is selected from one of wet-process ceramic paper, wet-process glass fiber mat, melamine foam, pre-oxidized fiber mat, and glass fiber mat.
5. The preparation method according to claim 1, characterized in that: The sealing device in step S3 is a thermostatic stainless steel tank with multiple valves; the alcohol reagent is selected from methanol and ethanol; and the hydrophobic modifier is hexamethyldisilazane.
6. The preparation method according to claim 5, characterized in that: The volume ratio of the alcohol reagent to the hydrophobic modifier in step S3 is 500:
1.
7. The preparation method according to claim 1, characterized in that: The mixture of hydrophobic modifier and alcohol reagent described in step S3 is introduced by self-absorption through the pressure difference between atmospheric pressure and the sealing device.
8. The preparation method according to claim 1, characterized in that: The process parameters for supercritical CO2 fluid drying in step S4 are: pressure 14 MPa, temperature 50-60℃, CO2 flow rate 2300 kg / h, and drying cycle time 4 hours.